A Case of a Pregnant Woman with Thrombosis in an Artificial Aortic Valve Resulting in Severe Cerebral Hemorrhage in the Newborn. (29th July 2018) - Kamei, Hidetake; Wakimoto, Yu; Murakami, Yumi; Omote, Maya; Harada, Kayoko; Fukui, Atsushi; Tanaka, Hiroyuki; Sawai, Hideaki; Shibahara, Hiroaki
Abstract : Many patients, after artificial valve replacement surgery, receive warfarin anticoagulant therapy. However, it has been reported that warfarin administration during pregnancy can cause fetal teratogenicity. With reference to this case, we will discuss how warfarin administration in mid-pregnancy caused severe cerebral hemorrhage in the newborn child. The 36-year-old patient in this case underwent aortic valve replacement surgery when she was 11 years old; this requires the continued use of warfarin after surgery. Although she was advised otherwise, the patient became pregnant. The warfarin treatment was discontinued at 5 weeks of gestation and she began self-injection of heparin; however, her health quickly deteriorated requiring an emergency, warfarin treatment. On gestation week 21, she was admitted to our hospital with a high likelihood of a spontaneous abortion. A week later, transesophageal ultrasonography revealed a thrombus in the patient's aortic valve. Because of this finding, we re-started warfarin administration. At 32 weeks of gestation, cardiotocography showed decreased fetal heart rate; thus, an emergency Cesarean section was performed. A baby was delivered, weighing 1, 702 g with an Apgar Score of 1 at 1 minute and 4 at 5 minutes. Cranial computed tomography of the infant showed bilateral intraventricular hemorrhage and ventricular dilation. In order to protect the mother and prevent hemorrhage in the newborn, it is recommended that a continuous heparin infusion should be administered to the pregnant woman after the 36th week of gestation. Regarding the impact on the infant, it is considered that continuous intravenous administration of heparin is safer during the third trimester of pregnancy. However, administration of heparin alone makes the preventive effect of thrombosis uncertain. When warfarin is administered in pregnancy, pregnancy management should be performed bearing the risk of fetal cerebral hemorrhage in mind.